PENATALAKSANAAN FISIOTERAPI PADA POST ORIF PLAT AND SCREW FRAKTUR FEMUR 1/3 DISTAL FEMUR DENGAN MODALITAS INFRA RED DAN PROPRIOCEPTIVE NEUROMUSCULAR FACILITATION - Pria Sandi Sinaga; Wahyu Wijanarko (Jurnal Gentle Birth, 2022)
Background: Fracture is a condition where there is discontinuity in the bone. The biggest causes of fractures are work accidents, traffic accidents, and so on. But it can also be caused by pathological or degenerative factors. Fractures can occur in any part of the body, including fractures in the distal 1/3 of the femur. The form of Physiotherapy services for Distal 1/3 Femur Fractures is to reduce edema, reduce pain, increase muscle strength, joint range of motion (LGS) and increase functional activity.  Objective: To find out the benefits of implementing physiotherapy in reducing edema in Distal 1/3 Femur Fractures, reducing pain, increasing muscle strength, increasing joint range of motion (LGS) and increasing functional activity of Femur Fractures. Conditions in Distal 1/3 Femur Fractures using Infrared Red and Propioceptive Neuromuscular Facilitation. . Hasil : Setelah dilakukannya terapi sebanyak 3 kali maka didapatkan hasil penilaian odem pada T1: 48,5cm menjadi T3 : 48 nyeri gerak  pada T1 : 6 menjadi T3 : 5, nyeri tekan pada T1 : 4 menjadi T3 : 3, nyeri diam T1 : 2 menjadi T3 : 1, peningkatan luas gerak sendi pada gerakan fleksi  T1 : 80 cm menjadi T3 : 85 cm, peningkatan kekuatan otot pda T1 : 3 menjadi T3 : 3+, dan peningkatan aktifitas fungsional pada T1 : 36 menjadi T3 : 32. Conclusion: Implementation of physiotherapy on Post ORIF Plate and Screw Fractures of Fe, Ur 1/3 Distal with Infra Red modalities, and Propioceptive Neuromuscular Facilitation can reduce edema, reduce pain, increase joint range of motion, increase muscle strength and increase the ability of functional activities.